The Implementation of Contextual Teaching and Learning in Arabic Language Instruction: A Case Study in Indonesia - Abdillah Rofiif Fatih Ritonga; Rifki Zaitul Ikhlas; Rahmat Hidayat; Dasrizal Dasrizal (Journal of Arabic Literature, Teaching and Learning, 2025)
Arabic language learning holds an important role in education in Indonesia. However, challenges such as differences in linguistic structure and complex vocabulary often hinder the learning process. This study aims to investigate how the implementation of contextual teaching and learning can enhance the quality of Arabic language instruction by making it more meaningful and relevant. Employing a qualitative case study approach, data were collected through observation, interviews, and document analysis. The findings reveal that the application of contextual teaching and learning includes the integration of everyday contexts, project-based learning, collaborative activities, and cultural exploration. Positive impacts observed include improved Arabic language proficiency, increased learning motivation, greater awareness of the importance of Arabic, the development of social and emotional skills, and students’ contextual understanding of Arab culture. The novelty of this study lies in applying contextual teaching and learning specifically to Arabic language learning in Indonesia, a field that has been rarely explored in depth. Unlike previous research that primarily focused on structural or grammatical challenges, this study emphasizes how contextual teaching and learning can integrate daily contexts, project-based learning, collaboration, and cultural exploration to make Arabic learning more meaningful and relevant. The findings provide new insights into enhancing language proficiency, learning motivation, and cultural awareness, while also demonstrating the potential of contextual teaching and learning to strengthen Islamic education through contextualized learning practices.